Uganda : 2006 Article IV Consultation and Staff Report for the 2006 Article IV Consultation, First Review of the Policy Support Instrument, Request for Waiver of Assessment Criteria, and Request for a Three-Year Policy Support Instrument; Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uganda. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This 2006 Article IV Consultation highlights that an acute electricity crisis threatens Uganda's macroeconomic performance. The regional drought in 2005/06 reduced Uganda's already inadequate hydropower-generating capacity, resulting in a production gap of nearly one-half of demand. The authorities have requested a new three-year policy support instrument in support of their near- and medium-term policies. The authorities' main objectives are to sustain macroeconomic stability while tackling the ongoing electricity crisis and addressing other infrastructure deficiencies to alleviate existing constraints on growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet